Implementation of Big Data in Learning in the Era of Industrial Revolution 4.0 - Muhammad Wahid Muhtadi; Ronggur Hasibuan; Yohanes William Kaunang; Emi Sita Eriana; Fajar Haditio (MultiTech Publisher, 2024)
The Industrial Revolution 4.0 has brought significant transformation in various sectors, including education. The use of Big Data in learning has become one of the main focuses in an effort to improve the quality of education, especially in vocational schools. Through a systematic review of relevant scientific literature, this study reveals the great potential of Big Data in learning personalization, student performance analysis, curriculum development, and improving the efficiency of managing educational institutions. However, it also identifies a number of challenges that need to be addressed, such as the lack of technological infrastructure, the lack of competence of educators, and the lack of supportive policies.The results of this study are expected to contribute to the development of more comprehensive education policies in the utilization of Big Data. In addition, this research is also expected to serve as a reference for education practitioners, technology developers and policy makers in an effort to improve the quality of education in the digital era.